2002
DOI: 10.1007/3-540-45708-9_34
|View full text |Cite
|
Sign up to set email alerts
|

The Filter-Combiner Model for Memoryless Synchronous Stream Ciphers

Abstract: Abstract.We introduce a new model -the Filter-Combiner modelfor memoryless synchronous stream ciphers. The new model combines the best features of the classical models for memoryless synchronous stream ciphers -the Nonlinear-Combiner model and the Nonlinear-Filter model. In particular, we show that the Filter-Combiner model provides key length optimal resistance to correlation attacks and eliminates weaknesses of the NF model such as the the Anderson leakage and the Inversion Attacks. Further, practical length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…It is not a basic instantiation of the Filter-Combiner model [26] since its nonlinear part has memory (128 bits of internal state), how-ever it belongs to the same family. According to [27], the use of cellular automata should improve the security of the cipher against some attacks using the specific properties of LFSRs.…”
Section: Overview Of the Hbb Ciphermentioning
confidence: 99%
See 1 more Smart Citation
“…It is not a basic instantiation of the Filter-Combiner model [26] since its nonlinear part has memory (128 bits of internal state), how-ever it belongs to the same family. According to [27], the use of cellular automata should improve the security of the cipher against some attacks using the specific properties of LFSRs.…”
Section: Overview Of the Hbb Ciphermentioning
confidence: 99%
“…Another contribution came from Sarkar at Crypto'02 [26]. He showed that some classical models for LFSR-based stream ciphers (Nonlinear Filter and Nonlinear Combiner) do not provide optimal security against Correlation Attacks [30].…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of HBB is that it replaces the classical LFSR (that has been used as a building block in most of the stream ciphers) by Cellular Automata (CA). It has been shown by the author of HBB previously that the classical LFSR based stream ciphers (either by using non-linear filter model or non-linear combiner model) are susceptible to correlation attack [19]. However, the Filter-Combiner model [19] can prevent many of the attacks on LFSR based models.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown by the author of HBB previously that the classical LFSR based stream ciphers (either by using non-linear filter model or non-linear combiner model) are susceptible to correlation attack [19]. However, the Filter-Combiner model [19] can prevent many of the attacks on LFSR based models. This model could not be realized with LFSR but could be realized with CA.…”
Section: Introductionmentioning
confidence: 97%
“…, s − 1, as input to produce a keystream bit. As analyzed by Sarkar [18], the filter combiner offers various advantages over the filter function and combinatorial generators. We show that in this case, the search space reduction and TMD attack can also be applied effectively.…”
Section: Introductionmentioning
confidence: 99%